2000
DOI: 10.1074/jbc.275.7.5179
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric-oxide Synthase (Type III) Is Activated and Becomes Calcium Independent upon Phosphorylation by Cyclic Nucleotide-dependent Protein Kinases

Abstract: Endothelial nitric-oxide synthase (NOS-III

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
197
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 271 publications
(209 citation statements)
references
References 54 publications
10
197
1
1
Order By: Relevance
“…Of the known phosphorylation sites on eNOS responsible for its activation, serine 1179 has been characterized most extensively (Chen et al, 1999;Fulton et al, 2002). Serine 1179 phosphorylation by PKA leads to activation of eNOS (Butt et al, 2000). We hypothesize that the mechanisms by which NO-cGMP-PKA pathway in the endothelium mediates vascular smooth muscle relaxation involve NO production through eNOS phosphorylation by PKA.…”
Section: Discussionmentioning
confidence: 95%
“…Of the known phosphorylation sites on eNOS responsible for its activation, serine 1179 has been characterized most extensively (Chen et al, 1999;Fulton et al, 2002). Serine 1179 phosphorylation by PKA leads to activation of eNOS (Butt et al, 2000). We hypothesize that the mechanisms by which NO-cGMP-PKA pathway in the endothelium mediates vascular smooth muscle relaxation involve NO production through eNOS phosphorylation by PKA.…”
Section: Discussionmentioning
confidence: 95%
“…Pretreatment of B-TECs with the membrane-permeable PKA inhibitory peptide myristoylated PKI [14][15][16][17][18][19][20][21][22] (10 minutes, 20 μmol/L) completely abolished AA-induced calcium entry in 99% of the cells tested (n = 84; Fig. 1; Table 1), suggesting a critical role of endogenous PKA in the activation of calcium signals by AA.…”
Section: Pka Is Required For Aa-induced Calcium Entry In B-tecsmentioning
confidence: 99%
“…PKA regulates eNOS activity through serine phosphorylation, and it has been recently reported that forskolin, a widely used adenylyl cyclase activator, is able to trigger proangiogenic effects through the PI3K, Akt, and eNOS pathways in human umbilical vascular ECs (21,22). In addition, it is worth noting that a number of different endothelial calcium-permeable channels are substrates for PKA phosphorylation, including some members of the transient receptor potential (TRP) superfamily of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms are mainly calcium-independent [20] and involve posttranslational modification by phosphorylation of eNOS at regulatory sites [21], messenger RNA (mRNA) stabilization [22], e.g., through heat shock protein 90 (hsp-90), and translocation [23]. NO produced in response to shear stress triggers vascular smooth muscle relaxation, inhibition of apoptosis [24], and inhibition of thrombocyte or monocyte adhesion [25].…”
Section: Introductionmentioning
confidence: 99%